(untitled) (Journal of Education and Development, 2023)
This study analyzes the lack of psychological support and follow-up for gymnasts motivated to compete in the Congolese championship. On the one hand, it calls into question the extent of social difficulties in light of current psychological suffering. On the other hand, it questions the fact that the athletes are dependent on their parents, who have no stable employment or have lost it with the onset of the COVID-19 epidemic. Despite this disastrous social situation, the sports system itself offers no guarantees in the face of athletes’ growing uncertainty. The analysis of this phenomenon on gymnasts revealed worrying psychological profiles in the Congolese sporting population, with mental pathologies emerging and developing insidiously. To enable a proper assessment of athletes’ mental strengths and weaknesses, our understanding shows that Target models of mental preparation would be more effective if psychopathologies were diagnosed first. We point to managerial irresponsibility in failing to take the psychosocial aspect seriously at a time when competitors are under pressure to achieve glory at all costs. Through observation of complaints against frustrations and, taking into account our conception of the structural model of the psyche, we found that athletes express themselves through a sad expression, both facial and verbal, to signal the emotional value of their agony. However, the desire to overcome this despair is marked by a costly defense that translates into a commitment to superstitious practices.